2020
DOI: 10.4103/jehp.jehp_583_20
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and job dissatisfaction as negative psychological barriers in school settings: A mixed-methods investigation of Iranian teachers

Abstract: BACKGROUND: Despite the multitude of studies comparing teacher burnout with an ample of variables, a need for seeking what English language teachers think about their job and the interfering variables regarding the context seems essential. The aim of this study was primarily to investigate the relationship between teacher burnout and job satisfaction of English language teachers and, then, to find out the impact of teaching experience and gender on teacher burnout and job satisfaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The possible reason could be that job dissatisfaction results from teachers’ high psychological demand and their low control over it ( Helms-Lorenz and Maulana, 2016 ) which then exposes them to frequent psychological loads that increase burnout and other health problems ( McCarthy et al, 2015 ). Although job dissatisfaction can result in discomfort, low self-esteem, sadness, and devaluation, all of which contribute to high levels of stress at work ( Wilhelm et al, 2000 ; Chaplain, 2001 ) and end up with WRB ( Atashpanjeh et al, 2020 ). The other possible explanation could be that teachers are expected to provide academic instruction, social–emotional support, and build relationships with students and families while often receiving inadequate compensation or support from administration and leadership, which can lead them to dissatisfaction and result in burnout development ( Stauffer and Mason, 2013 ; Nantsupawat et al, 2017 ; Atashpanjeh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The possible reason could be that job dissatisfaction results from teachers’ high psychological demand and their low control over it ( Helms-Lorenz and Maulana, 2016 ) which then exposes them to frequent psychological loads that increase burnout and other health problems ( McCarthy et al, 2015 ). Although job dissatisfaction can result in discomfort, low self-esteem, sadness, and devaluation, all of which contribute to high levels of stress at work ( Wilhelm et al, 2000 ; Chaplain, 2001 ) and end up with WRB ( Atashpanjeh et al, 2020 ). The other possible explanation could be that teachers are expected to provide academic instruction, social–emotional support, and build relationships with students and families while often receiving inadequate compensation or support from administration and leadership, which can lead them to dissatisfaction and result in burnout development ( Stauffer and Mason, 2013 ; Nantsupawat et al, 2017 ; Atashpanjeh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our research focuses more on the academic burnout of trainee teachers, so we believe that it is important to concentrate on stress factors related to the educational environment, and these factors should play a major role in the development of burnout. In various studies,[ 15 ] we mainly find sources of organizational stress, although individual variables may also have an impact on perceived stress. [ 16 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
“… Fiorilli et al (2017) , taking 149 Italian primary school teachers as participants, found teachers were at risk of highly intense burnout syndrome and that teacher burnout partially mediated the relationship between emotional intensity and satisfaction with social support received. Atashpanjeh et al (2020) found a moderate negative correlation between teacher burnout (emotional exhaustion and depersonalization) and job satisfaction, based on a mixed-methods study conducted on 103 teachers in Iran.…”
Section: Teacher Burnoutmentioning
confidence: 99%